ByzRev 07.2025.010: Claire Vernon, From Byzantine to Norman Italy:: Mediterranean Art and Architecture in Medieval Bari (New Directions in Byzantine Studies). London: I. B. Tauris 2023. - Katz, Dana (The Byzantine Review, 2025)
Claire Vernon, From Byzantine to Norman Italy: Mediterranean Art and Architecture in Medieval Bari (New Directions in Byzantine Studies). London: I. B. Taurus 2023. xii + 269 pp. 137 ill., 4 maps. – ISBN 978-1-7883-1506-7 (hb). £76.50 (hb), £20.87 (e-book).